IDENTIFICATION OF POTENTIAL HAZARDS AND RISK ASSESSMENT IN PORK MEAT PRODUCTS OF PESANGGARAN SLAUGHTERHOUSE - Berutu, Fazral Anshari; Suardana, I Wayan; Suada, I Ketut (Buletin Veteriner Udayana, 2022)
At each step in the abattoir there are many opportunities for contamination of pig carcasses with potentially pathogenic bacteria. There are processes that reduce the number of bacteria, but do not completely eliminate them. This study aims to identify the potential hazards and risks of pork products at the Pesanggaran Slaughterhouse. This study used the observation method which was carried out 15 times, namely direct field observations (inspections) and interviews to obtain data. The data is then analyzed by Failure Modes and Effect Analysis (FMEA) in determining the potential hazards and risk assessment. The results showed that there were 15 potential hazards in pork products at the Pesanggaran Slaughterhouse. The Risk Assessment Code (RAC) values for these potential hazards are 9 potential hazards having an RAC value of 1, 2 potential hazards having an RAC value of 2 and 4 potential hazards having an RAC value of 4. All potential hazards are categorized as unacceptable potential hazards. These potential hazards must be eliminated by the Pesanggaran Slaughterhouse to avoid the spread of infectious diseases through food (foodborne disease).